Notícia: a variação de um gênero mediada pelo contexto - Silva, Pollyanna Honorata (2016)
This paper aims to contribute to the studies located in Textual Linguistics, regarding the description and characterization of genres, defined by Travaglia (2007) and Bakhtin (1997)´s theory. From the assumption that genres vary, since they are "relatively stable types of utterances" (BAKHTIN, 1997), we have the basic research question: why is that the news, understood as a specific textual genre, have variations in their composition? To answer this question, we take as an analytical corpus the newspaper Folha de S. Paulo´s news. When necessary, for the purpose of comparison contexts we also analyze other newspapers. We have as goals of the research: to verify the relationship between the news and the context of interaction in which journalists and readers / audience are inserted; to analyze the relationship between the context and structural variations (superstructure and other aspects), linguistic and other kinds which can be found in the news, seeking its relationship with the (s) context (s); to analyze the categories of superstructure in the news which are present in the corpus, relating the presence of variation in these categories to the categories of theoretical framework adopted in the context; to check in which context categories are more relevant in the composition of news and its variations. We take the assumption that the variation of news occurs due to context, understood as a context model, as sociocognitive theory proposed by Van Dijk (2012). According to the author, the social situation in its totality does not correspond to the communication context, which is understood as a mental model that consists of categories that express the most important aspects of the social situation for the production and comprehension of speech. This definition of context integrates cognitive elements such as subjective mental models; and social, which correspond to the cultural knowledge acquired by partners in social interaction. In this perspective, Van Dijk (2012) proposes as basic contextual categories of context model: 1. Environment 2. I-myself, 3. Participants 4. Actions / Events. The category I-myself it is central, because it refers to the producer of the speech, with their ideologies, objectives and communicative intentions, elements responsible for much of the variations of speech. Our results show that the categories that influence the variation in the news are: I-myself, as the journalist's goals at the micro level, and the environment, also at the micro level, the latter being responsible for defining the thematic content (BAKHTIN, 1997 and TRAVAGLIA, 2007b), mainly from the news of Tourism folder. In terms of variation in the elements of linguistic surface and compositional structure (TRAVAGLIA, 2007b), we have as main results: the news becomes predominantly descriptive or argumentative, argumentative (not narrative) when the purpose of the I-myself even at the micro level, it is to sell the reported object, not disclose an event to the population. Additionally, the more relevant in the context model is the goal of selling the categories of textual superstructure that appear the most are Comments and Details of Main Event, which shows a rather atypical news configuration, since the news prototypical starts with the Lead, followed by background , and usually shows few comments. Besides the purpose of selling , the analysis showed other objectives related to the category – I-myself influencing variations in the composition of news , namely: to guide / advise ; to schedule an ideological place ; to comment on a cultural event and comment on a sporting event. We also show in our analysis that many variations in the news are related to market logic and submission of Journalism to the interests of capital, as shown by Marshall (2005). KEY-WORDS: News; Context; Variation.